Exploring the implications of item-level data in sex offenders' maintenance polygraph results. Issue 1 (2nd January 2022) - Lin, Jeffrey; Hisscock, Greg; Simon, Walter
ABSTRACT: The maintenance polygraph is used to assess sex offenders' compliance with treatment and supervision requirements in the community. Existing research on the utility of this practice focuses on overall exam outcomes and effects, without analysing the disclosures that sex offenders make or the questions that cause failed and inconclusive outcomes. This study analyses item-level data from Denver, Colorado on disclosures and questions to assess the tension between the maintenance polygraph's contribution to public safety and potential negative consequences such as inaccurate outcomes, financial cost, conflict of interest concerns, and the reinforcement of social disadvantage. We find that subjects rarely make serious disclosures during the exam process and that a substantial portion of subjects must retake the exam despite not registering as deceptive on any question. Findings suggest that in order to best determine the utility of the maintenance polygraph for different types of sex offenders, decision-makers should consider item-level data in their assessments.